A new cross-section layout method and geometrical parameter optimization for floor beams of rack car body considering modal factors - Yin, Xiangyun; Chen, Ruiwen; Song, Yanxuan; Yin, Guofu (Structural and multidisciplinary optimization, 2024)
Reducing the weight of floor beams is a promising way to carry out the lightweight design of the rack car body. However, the reduction will generally amplify the vibration of the car body chassis transmitted to the floor and cause a decrease in riding comfort. Moreover, the lightweight design of the rack floor beams still depends on engineer’s experiences. To address the issues, a cross-section layout method combing bionic with multi-objective topology optimization was proposed. According to the method, a novel bionic layout of rack floor beams offering out-standing reducing weight, vibration performance, in which the configuration elements of bionic quasi-ellipses replaced traditional straight lines in their cross-sections, was proposed. Firstly, a finite element modeling under multiple load cases for rack floor beams was built. Secondly, we screened an optimal load path using a multi-objective topology optimization method considering modal factors, and then constructed a novel bionic layout of cross-sections from beetles. Subsequently, considering minimizing the total mass (M) while maximizing the first-order vertical bending modal frequency (FVBMF) as two optimization objectives, a surrogate-based multi-objective genetic algorithm (SMOGA) and the technique for order of preference by similarity to ideal solution (TOPSIS) were then utilized in sequence to construct the surrogate models, solve optimization process for geometrical parameters of the cross-section, and identify the best trade-off design. Moreover, the multi-objective geometrical parameter optimization under multiple load cases were investigated. The results show that the parameter tt has a more significant influence on the mass and modality of floor beams, and the parameter b a s e l i n e _ a r c should be less than 80 mm under single load cases (SLCs). Finally, the dynamic and static performance comparison of the proposed cross-section with the traditional cross-section were also performed. The weight of the optimum outcomes is reduced by 13.25 % and the 1-order vertical natural frequency is significantly increased by 48.04 % . The results show that the proposed floor beams have significant modal performance and better weight reduction.